Chemical Investigation of the Seeds of Adenanthera pavonina Linn. - Chourasia, O.P.; Rao, J.T. (Asian Journal of Chemistry, 2010)
The reducing sugars present in the seeds of Adenanthera pavonina Linn are 3.16 per cent (as lucose) containing D-arabinose, D-glucose, D-rhamnose and D-xylose. The percentages of various amino acids present in the crude protein (4.5%) were found to be: alanine (6.96%), aspartic acid (14.17%), cystine (4.64%), glutamic acid (20.33%), glycine (4.64%), leucine (11.49%), methionine (6.50%), proline (8.25%), serine (7.66%) and tyrosine (6.74%).